Literacy: A Lifelong Process Through a Balanced Literacy Approach - Зої Т. Апостолоу (Hryhorii Skovoroda University in Pereiaslav, 2023)
This paper attempts a critical analysis of literacy acquisition by preschool children through a balanced literacy approach, a mixed method which brings together elements from methods with an emphasis on code and from methods with an emphasis on meaning. In particular, visuals of a balanced literacy approach, as it takes place (or not) in Greek preschool education classes, are presented. Individual issues, challenges and perspectives which are introduced by this method are explored in comparison and in correspondence with the traditional and outdated understanding of literacy, which links it to learning to read and write. Emphasis is made on the strengths and weaknesses of a balanced literacy approach in order to highlight the prospects for its application in early childhood education on a larger scale. Questions and concerns are raised regarding the expansion and application of the method and its acceptance by Greek kindergarten teachers. However, the need for the application of a balanced literacy approach in early childhood education classes is reflected, as the only method that combines, adopts and utilizes elements of many methods, able to offer young students sufficient resources in the course of mastering literacy.